Investigating the Effect of Brand Consciousness on Cognitive, Affective and Conative Brand Loyalty - Fouad Salem, Suha; Binti Mohd Talib, Zunirah (International Journal of Psychosocial Rehabilitation, 2020)
The current study was aimed to examine the effects of brand consciousness and brand love on different types of brand loyalty in respect to fast fashion industry. A total of 300 usable responses obtained via a self-structured questionnaire were analyzed using the structural equation modeling approach. The findings demonstrate that all hypotheses with regard to the link between brand consciousness, brand love, and stages of brand loyalty were supported. Nonetheless, the link between the brand consciousness and affective loyalty as well as conative loyalty was not supported in which brand consciousness had indirect effect on affective loyalty and conative loyalty through brand love. Notably, the current study is the first to report the impact of brand consciousness and brand love on every level of brand loyalty within the setting of the fast fashion industry. The results of the study are promising to facilitate the sellers in establishing effective brand positioning and marketing approaches for being viable in the market.